Study on weldability window and interface morphology of steel tube and tungsten alloy rod welded by explosive welding. (November 2019) - Baoxiang, Ren; Gang, Tao; Peng, Wen; Changxing, Du
Abstract: The explosive welding of the axisymmetric 30CrMnSi tube and tungsten alloy rod was studied. Through theoretical analysis, the weldability window of these two metals was obtained, which could enable the prediction of the welding interface morphology under different explosive conditions. The explosive welding tests under different explosive loading conditions were carried out and 30CrMnSi/tungsten alloy composite rods were obtained. Analytical investigations of the microstructure, hardness, and composition of the samples were performed. The results showed that 30CrMnSi steel tubes and tungsten alloy rods could be successfully welded together. The welding interfaces of composite rods obtained under different explosive loads had different morphological characteristics. With the increase in the explosive load, the welding interface transforms from a straight interface to a corrugated one and even forms a melting transition zone at the interface. The chemical compositions of the transition zone showed that the region consists of two kinds of welded materials. It indicated that the temperature at the interface during the welding process exceeded the melting temperature of the tungsten alloy, and both of the welded materials generated melting phenomena. Highlights: The explosive welding of 30CrMnSi steel tube and tungsten alloy rod was studied The influence of the explosive load on the welding interface morphology was studied The temperature at the welding interface exceeded the melting temperature of the tungsten alloy There was no significant increase in the hardness of the tungsten alloy at the weld interface